Exceptionally Heavy Doping Boosts the Performance of Iron Silicide for Refractory Thermoelectrics. Issue 18 (23rd March 2022) - Qiu, Pengfei; Cheng, Jun; Chai, Jun; Du, Xiaolong; Xia, Xugui; Ming, Chen; Zhu, Chenxi; Yang, Jiong; Sun, Yi‐Yang; Xu, Fangfang; Shi, Xun; Chen, Lidong
Abstract: Thermoelectric (TE) power generation is expected to be one of the most effective solutions to convert industrial exhaust heat to electricity for conserving fossil energy and reducing carbon emissions. However, its real application is obstructed decisively by the weakness of the service stability of state‐of‐the‐art TE materials at high temperatures in air. Refractory iron silicide (β‐FeSi2 ) used to be widely investigated as TE materials, but the low zT has restricted its practical application and even made it almost vanish from TE research in recent years. Here, guided by theoretical calculation, ultrahigh solubility of Ir on the Fe sites of β‐FeSi2 is successfully realized. Doping 16% Ir elicits multi‐valley electrical conduction and phonon‐electron scattering, doubling the previous zT record of β‐FeSi2 to ≈0.6 at 1000 K. The TE properties of the obtained β‐FeSi2 are practically unchanged after thermal aging in air at 1173 K. The new conceptual electrode‐less β‐FeSi2 ‐based refractory module demonstrates considerable power density and stable power generation when it is burned by a gas flame in air. These results mark a step toward developing practical TE power generation technology for the recovery of industrial waste heat. Abstract : Guided by theoretical calculation, ultrahigh solubility of Ir on the Fe sites of β‐FeSi2 is realized. Doping 16% Ir elicits multi‐valley electrical conduction and phonon‐electron scattering, doubling the previous zT record of refractory β‐FeSi2 to ≈0.6 at 1000 K. The new conceptual electrode‐less β‐FeSi2 ‐based refractory module demonstrates stable power generation when it is burned by a gas flame in air.